FACTORS AFFECTING STUDENT LEARNING OUTCOMES IN ACCOUNTING EDUCATION PROGRAMS CLASS XI SOCIAL SCIENCES ( IPS ) IN SMA 2 ISLAND DHARMASRAYA ARBOR - Maswita, Ringga; Tanjung, Mirna; Dewita Hia, Yulna (Pendidikan Ekonomi, 2014)
This research was conducted at SMAN 2 Island Dharmasraya Arbor regarding the effect of study habits and students motivation toward learning difficulties accounting Class XI students of the Department of Social Sciences ( IPS ) at SMAN 2 Island Dharmasraya Arbor . The purpose of this study is to obtain empirical evidence about the influence of study habits and students motivation toward learning difficulties accounting students XI Class Department of Social Sciences ( IPS ) at SMAN 2 Island Dharmasraya Arbor The method used in this research is descriptive and causative . This research is a saturated or census sampling , where the population sampled totaling 89 students from a population of 89 students . Data habit learning ( X1 ) and motivation ( X2 ) is obtained from the results of a questionnaire or a questionnaire while studying accounting students hail of data ( Y ) views of student learning and the results of interviews with students . Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of classical assumption test , multiple regression analysis and hypothesis testing . The results of this study indicate that : 1 . Habit learning significant and positive impact on learning outcomes of accounting students XI Class Department of Social Sciences ( IPS ) at SMAN 2 Island Dharmasraya Arbor , 2 . Motivation students learn significant and positive impact on learning outcomes of accounting Class XI students of the Department of Social Sciences ( IPS ) at SMAN 2 Dharmasraya Arbor Island , 3 . habit learning and student motivation jointly significant effect on the results of Class XI students studying accounting Department of Social Sciences ( IPS ) in SMA 2 Island Dharmasraya Arbor . students in the learning process in an attempt to further optimize the learning outcomes of accounting students of class XI of SMAN 2 Island Dharmasraya Arbor . From the results of hypothesis testing can be concluded that the habit of learning and student motivation significantly influence accounting student learning outcomes , meaning that the higher the higher the habit of learning and motivation to study the learning result will be higher , with increased learning outcomes obtained by students means students could conquer the learning outcomes that it faces .Â